2021
DOI: 10.1097/md.0000000000026562
|View full text |Cite
|
Sign up to set email alerts
|

Serum pepsinogen II levels are doubled with Helicobacter pylori infection in an asymptomatic population of 40,383 Chinese subjects

Abstract: Pepsinogen (PG) I and II are crucial in the gastric digestive processes. This study is to examine the relationship of serum PGI, PGII, and PGI/PGII ratio with Helicobacter pylori (Hp) infection, age, sex, and body mass index (BMI) in subjects in Beijing, China. A total of 40,383 asymptomatic subjects, who underwent medical examination in Beijing Rehabilitation Hospital, were included in this study. Serum PG levels were measured using chemoluminescence techniques. The age, sex,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
12
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 29 publications
4
12
2
Order By: Relevance
“…H. pylori is considered as a primary carcinogen 12 . According to the studies about H. pylori infection carried out in China, in H. pylori ‐positive patients, the serum levels of G17, PGI and PG II increase, especially PGII, while the ratio of PGI/PGII decreases 13 . This study identified that the level of G17 in H. pylori ‐positive subjects was remarkably higher than that in H. pylori ‐negative subjects, coinciding with another study 14 .…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…H. pylori is considered as a primary carcinogen 12 . According to the studies about H. pylori infection carried out in China, in H. pylori ‐positive patients, the serum levels of G17, PGI and PG II increase, especially PGII, while the ratio of PGI/PGII decreases 13 . This study identified that the level of G17 in H. pylori ‐positive subjects was remarkably higher than that in H. pylori ‐negative subjects, coinciding with another study 14 .…”
Section: Discussionsupporting
confidence: 80%
“…12 According to the studies about H. pylori infection carried out in China, in H. pylori-positive patients, the serum levels of G17, PGI and PG II increase, especially PGII, while the ratio of PGI/PGII decreases. 13 This study identified that the level of G17 in H. pylori-positive subjects was remarkably higher than that in H. pylorinegative subjects, coinciding with another study. 14 Patients with H. pylori infection and low PGI/PGII ratio are confronted with a higher risk of gastric cancer, and thus secondary diagnosis (endoscopy and histology) should be performed.…”
Section: Correlation Analysis Between G17 and Pgsupporting
confidence: 86%
See 1 more Smart Citation
“…2, the levels of PG-I measured by CLIA increased with age but gradually decreased after age 60, similar to Sun's ndings [20]. However, the levels of PG-I measured by ELISA consistently increased with age, similar to Hong's results [22]. Although serum pepsinogen concentrations were well correlated with acid secretion [25], the effect of age on gastric acid secretion is controversial.…”
Section: Discussionsupporting
confidence: 74%
“…It has been reported that PGI and II are increased and PGI/PGII is decreased in patients with H. pylori infection, and that PGI and PGII are decreased and PGI/PGII is increased after the eradication of H. pylori . [ 27 , 28 ] In this study, the PG I and II levels of the 11 participants with new H. pylori infections tended to increase after infection; however, the difference in PG levels was not significant. In addition, the results indicated that PG I/PG II significantly decreased after infection (PG I: 71.7 ± 7.47 in 2010 and 78.7 ± 11.0 in 2015, p = 0.61; PG II: 10.3 ± 1.49 in 2010 and 21.6 ± 5.79 in 2015, p = 0.07; and PG I/PG II: 7.49 ± 0.83 in 2010 and 4.31 ± 0.30 in 2015, p < 0.01).…”
Section: Discussioncontrasting
confidence: 52%